Neo-industrial Base of Network Social Prosperity in the Russian Economy; Procedia - Social and Behavioral Sciences; Vol. 166 : Proceedings of The International Conference on Research Paradigms Transformation in Social Sciences 2014 (RPTSS-2014), 16–18 October 2014, Tomsk, Russia - Gasanov M. A. Magerram Ali Ogly (2015, 2015)
Title screen